2013
DOI: 10.1177/0023677213492509
|View full text |Cite
|
Sign up to set email alerts
|

Oestrus cycle of the Desert hamster (Phodopus roborovskii, Satunin, 1903)

Abstract: The Desert hamster, Phodopus roborovskii, is one of the lesser-known laboratory animal models and therefore knowledge of its reproductive system and physiology is limited. This study investigated the time course of vaginal and behavioural oestrus cycles by means of vaginal smear cytology, serum luteinizing hormone (LH) levels, wheel-running activity patterns, and pairing tests. The oestrus cycle lasts between four and six days and follows a pattern rather similar to that described for other rodent species. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…For the first time, we present details about spermatogenesis and the morphological characteristics of male reproductive organs and sperm cells at different stages in the Roborovski hamster. Following the detailed descriptions of the female estrous cycle, 20 our study advances the understanding of the complexity of the reproductive system in hamsters. Furthermore, we present a novel tool to analyze the DCSE of the Roborovski hamster that can be easily adapted to understand the DCSE of other species.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For the first time, we present details about spermatogenesis and the morphological characteristics of male reproductive organs and sperm cells at different stages in the Roborovski hamster. Following the detailed descriptions of the female estrous cycle, 20 our study advances the understanding of the complexity of the reproductive system in hamsters. Furthermore, we present a novel tool to analyze the DCSE of the Roborovski hamster that can be easily adapted to understand the DCSE of other species.…”
Section: Discussionmentioning
confidence: 96%
“…[15][16][17] Previous studies found that SARS, 1 of the 3 epidemic coronaviruses to emerge in the past 20 years and that shows similar clinical presentations to COVID-19, 18 could cause orchitis 19 and focal testicular atrophy. 20 Considering the tens of millions of COVID-19 cases and that men are more vulnerable to COVID-19 than women, [21][22][23] it is imperative to determine the effect of COVID-19 on male reproduction. 24 Several studies have been performed on this topic.…”
Section: Introductionmentioning
confidence: 99%